Study of Social, Economic, and Environmental Impacts of Inter-Island Bridge Construction in Belakang Padang and Mat Belanda - Kenny Kenny; Ade Jaya Saputra (Fakultas Teknik Sipil dan Perencanaan, 2023)
The research examines the social, economic, and environmental impacts of constructing an inter-island bridge between Belakang Padang and Pulau Mat Belanda. The findings reveal that the bridge has significant social benefits, enhancing inter-island access and improving the quality of life for local communities. Additionally, it brings positive economic impacts, including increased trade activities and improved distribution efficiency. However, responsible management must address potential environmental effects during construction and operation. The construction of the inter-island bridge provides substantial social advantages by facilitating improved accessibility and connectivity. It allows for smoother movement of people, goods, and services, thereby enhancing the quality of life for residents of Belakang Padang and Mat Belanda Island. The bridge fosters closer relationships, cultural exchange, and the development of vibrant inter-island communities. Furthermore, the bridge contributes to economic growth and prosperity. Enhanced inter-island connectivity stimulates trade activities and opens new markets, benefiting local businesses and the economy. The efficient transportation of goods and services leads to increased commerce, generating economic opportunities for both islands. While acknowledging the positive aspects, it is essential to address potential environmental impacts. Proper management measures must be implemented during construction and operation to mitigate adverse effects. Environmental considerations include habitat disruption, water pollution, and noise pollution. By adopting sustainable practices and responsible operation, the potential environmental risks can be minimized, ensuring the preservation of the ecosystem. In conclusion, the construction of the inter-island bridge in Belakang Padang and Pulau Mat Belanda brings significant social and economic benefits. It improves accessibility, strengthens social bonds, fosters economic growth, and enhances trade activities. However, responsible environmental management is crucial to mitigate potential negative impacts. By incorporating sustainable practices, this development can positively impact the lives of local communities while preserving the environment.